Palm oil mill effluent as a potential medium for microalgae Chlorella sp. cultivation for lipid production - Karthick Murugan, Palanisamy; Primilla, Paramasivam; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim; Rameshprabu, Ramaraj; Natanamurugaraj, Govindan (School of Renewable Energy, Maejo University, 2020)
Fresh water microalgae Chlorella sp. was isolated from water body of Taman Gelora, Kuantan, Pahang. The isolated monoculture was cultured in different concentration of POME (10%, 20%, 30%, 40% and 50%, v/v) as substrate. The maximal growth and biomass productivity found in 30% (v/v) of POME. The maximal dry biomass 1.56 g/L was obtained and extracted 39.1% lipid which approximate similar productivity as in conventional BG-11 medium 1.65 g/L of biomass and 41.5% lipid was obtained. Gas chromatography mass spectrometry analysis shown composition of fatty acid such as linolelaidic acid, oleic acid, palmitic acid, stearic acid, elaidic acid and α-linoleic acid as dominant. Highest fatty acid has found to be linolelsidic acid (41.69%). POME has potential to be used as a substrate for microalgae Chlorella sp. cultivation.